The institutionalisation of memory in the former Clandestine Detention Center La Perla (1983-2007) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The article reconstructs the process of conquest of the former Clandestine Detention, Torture and Extermination Center La Perla as a Site of Memory and Promotion of Human Rights, at the same time, it analyzes the articulations between actors that parti- cipate in human rights organizations and State, the development of public policies and the struggles for the senses of the past in the public space. To that purpose, the first and second sections present the modalities of visibility and registration of La Perla in the public arena since the return of democracy until 2003. The third section, located on the thirtieth anniversary of the military coup (1976-1983), explains the development of a policy of memory in the province of Córdoba and the recovery of that particular site. It is interesting to show the changes in public policies around the sites that worked as clandestine detention centers during State terrorism and the central place they occupy in the construction and transmission of the official memory of the recent past.
Keywords: Public politics; Public memory; Clandestine Detention Centers; Sites of Memory.